Recombinant FOXN1 fusion protein increases T cell generation in old mice - Zhao, Jin; Hu, Rong; Lai, Kuan Chen; Zhang, Zhenzhen; Lai, Laijun (Frontiers in Immunology, 2024)
T cell development in the thymus is dependent on the thymic microenvironment, in which thymic epithelial cells (TECs) are the major component. However, TECs undergo both a qualitative and quantitative loss during aging, which is believed to be the major factor responsible for age-dependent thymic atrophy. FOXN1 plays a critical role in TEC development and adult TECs maintenance. We have previously reported that intrathymic injection of a recombinant (r) protein containing murine FOXN1 and a protein transduction domain increases the number of TECs in mice, leading to enhanced thymopoiesis. However, intrathymic injection may not be an ideal choice for clinical applications. In this study, we produced a rFOXN1 fusion protein containing the N-terminal of CCR9, human FOXN1 and a protein transduction domain. When injected intravenously into 14month-old mice, the rFOXN1 fusion protein enters the thymus and TECs, and enhances thymopoiesis, resulting in increased T cell generation in the thymus and increased number of T cells in peripheral lymphoid organ. Our results suggest that the rFOXN1 fusion protein has the potential to be used in preventing and treating T cell immunodeficiency in older adults.